The Value Of Field Measurement In The Design And Construction Of Deep Foundations ? Synopsis - J. P. Burland (Deep Foundations Institute, 2010)
The paper describes a number of recent case histories in the United Kingdom where field instrumentation and measurements have played a major role in the design and construction of excavations, piles and foundations. It is shown that the design and construction procedures for deep excavations in London Clay are based almost entirely on the results of field measurements. Examples are given of successful application of such measurements. The present understanding of the behaviour of bored piles in stiff clays and their design is based on a number of instrumented pile loading tests. The results of these tests have led to a radically new concept of pile design in which the piles operate at their full shaft capacity under working loads thereby resulting in considerable savings in design and construction. Some examples of the successful application of this concept are given. Finally it is shown that the present knowledge of the stiffness properties of chalk is based entirely on field observations. An example is given of how direct field measurements were used to solve a foundation problem at the base of a coffer-dam in chalk.